2024
DOI: 10.1002/aenm.202400851
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Redistribution Triggered Surface Adsorption and Mass Transfer to Boost Electrocatalytic Glycerol Upgrading Coupled with Hydrogen Evolution

Zhefei Zhao,
Xinyi Shen,
Xingyu Luo
et al.

Abstract: Electrocatalytic glycerol oxidation reaction (GOR) stands out as an economical and prospective technology to replace oxygen evolution reaction for co‐producing high‐valued chemicals and hydrogen (H2). Regulating the adsorption of glycerol (GLY) and hydroxyl (OH) species is of great significance for improving the GOR performance. Herein, a hierarchical p–n heterojunction by combining Co‐metal organic framework (MOF) nanosheets with CuO nanorod arrays (CuO@Co‐MOF) is developed to realize the optimization on GOR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
(58 reference statements)
4
5
0
Order By: Relevance
“…Upon increasing the potential from 1.03 to 1.63 V vs. RHE, the intensity of the characteristic peak associated with Co 2+ gradually diminished, while the band corresponding to CoOOH at 600 cm À1 intensified. 136 This observation confirmed the phase reconstruction from Co-MOF (Co 2+ ) to CoOOH (Co 3+ ), elucidating the transformation of the active catalyst structure during glycerol oxidation. 136 Song et al conducted an X-ray photoelectron spectroscopy (XPS) study to uncover the active catalyst structure of NiCo-61-MOF during benzyl alcohol oxidation.…”
Section: Active Catalyst Structure Of Mofs For Aorsupporting
confidence: 72%
See 4 more Smart Citations
“…Upon increasing the potential from 1.03 to 1.63 V vs. RHE, the intensity of the characteristic peak associated with Co 2+ gradually diminished, while the band corresponding to CoOOH at 600 cm À1 intensified. 136 This observation confirmed the phase reconstruction from Co-MOF (Co 2+ ) to CoOOH (Co 3+ ), elucidating the transformation of the active catalyst structure during glycerol oxidation. 136 Song et al conducted an X-ray photoelectron spectroscopy (XPS) study to uncover the active catalyst structure of NiCo-61-MOF during benzyl alcohol oxidation.…”
Section: Active Catalyst Structure Of Mofs For Aorsupporting
confidence: 72%
“…136 This observation confirmed the phase reconstruction from Co-MOF (Co 2+ ) to CoOOH (Co 3+ ), elucidating the transformation of the active catalyst structure during glycerol oxidation. 136 Song et al conducted an X-ray photoelectron spectroscopy (XPS) study to uncover the active catalyst structure of NiCo-61-MOF during benzyl alcohol oxidation. 134 The XPS spectra of NiCo-61-MOF on nickel foam revealed that the Ni 2p 3/2 peak experienced a slight shift to a higher binding energy of 856.37 eV after benzyl alcohol oxidation, compared to the fresh electrocatalysts with a binding energy of 856.17 eV.…”
Section: Active Catalyst Structure Of Mofs For Aorsupporting
confidence: 72%
See 3 more Smart Citations